Gaming houses and esports stadiums Architecture for electronic sports - Vidalón, Jhoan (2023)
Electronic sports (e-sports) have had a huge international impact in recent years and form a massive phenomenon. The growing interest of millions of players around the world motivated by the practice of electronic sports has led to the construction of buildings that facilitate their development. Some are the so-called gaming houses, places to train and accommodation for athletes. Others are the esport stadiums, which are the equivalent of coliseums where the competitions are held. The last ones are being built in greater quantity and with greater dimensions each time, for events of enormous attendance. In Peru, although there are a large number of people who practice esports, large buildings have not yet been built for these recreational sports. It is in this panorama of technological platforms that the work of architects and designers opens up to new possibilities: to produce the virtual settings of each videogame and, on the other hand, to project buildings where electronic athletes can train and compete in a professional manner.